Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To determine which equation best compares the [tex]$y$[/tex]-intercepts of the functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex], we need to find the [tex]$y$[/tex]-intercepts of both functions and then compare them.
1. Determine the [tex]$y$[/tex]-intercept of [tex]\( f(x) \)[/tex]:
The [tex]$y$[/tex]-intercept of [tex]\( f(x) \)[/tex] is found by evaluating the function at [tex]\( x = 0 \)[/tex]:
[tex]\[ f(0) = -6 \cdot (1.02)^0 \][/tex]
Since [tex]\( (1.02)^0 = 1 \)[/tex]:
[tex]\[ f(0) = -6 \cdot 1 = -6 \][/tex]
Thus, the [tex]$y$[/tex]-intercept of [tex]\( f(x) \)[/tex] is [tex]\( -6 \)[/tex].
2. Determine the [tex]$y$[/tex]-intercept of [tex]\( g(x) \)[/tex]:
From the given table, the value of [tex]\( g(x) \)[/tex] when [tex]\( x = 0 \)[/tex] is [tex]\( -3 \)[/tex].
[tex]\[ g(0) = -3 \][/tex]
Thus, the [tex]$y$[/tex]-intercept of [tex]\( g(x) \)[/tex] is [tex]\( -3 \)[/tex].
3. Compare the [tex]$y$[/tex]-intercepts:
- [tex]\( y \)[/tex]-intercept of [tex]\( f(x) = -6 \)[/tex]
- [tex]\( y \)[/tex]-intercept of [tex]\( g(x) = -3 \)[/tex]
Now, we need to check the given comparisons:
- The [tex]$y$[/tex]-intercept of [tex]\( f(x) \)[/tex] is equal to the [tex]$y$[/tex]-intercept of [tex]\( g(x) \)[/tex].
[tex]\[ -6 = -3 \quad \text{(False)} \][/tex]
- The [tex]$y$[/tex]-intercept of [tex]\( f(x) \)[/tex] is equal to 2 times the [tex]$y$[/tex]-intercept of [tex]\( g(x) \)[/tex].
[tex]\[ -6 = 2 \cdot (-3) = -6 \quad \text{(True)} \][/tex]
- The [tex]$y$[/tex]-intercept of [tex]\( g(x) \)[/tex] is equal to 2 times the [tex]$y$[/tex]-intercept of [tex]\( f(x) \)[/tex].
[tex]\[ -3 = 2 \cdot (-6) = -12 \quad \text{(False)} \][/tex]
- The [tex]$y$[/tex]-intercept of [tex]\( g(x) \)[/tex] is equal to 2 plus the [tex]$y$[/tex]-intercept of [tex]\( f(x) \)[/tex].
[tex]\[ -3 = -6 + 2 = -4 \quad \text{(False)} \][/tex]
Therefore, the correct comparison is:
[tex]\[ \text{The $y$-intercept of \( f(x) \) is equal to 2 times the $y$-intercept of \( g(x) \)}. \][/tex]
1. Determine the [tex]$y$[/tex]-intercept of [tex]\( f(x) \)[/tex]:
The [tex]$y$[/tex]-intercept of [tex]\( f(x) \)[/tex] is found by evaluating the function at [tex]\( x = 0 \)[/tex]:
[tex]\[ f(0) = -6 \cdot (1.02)^0 \][/tex]
Since [tex]\( (1.02)^0 = 1 \)[/tex]:
[tex]\[ f(0) = -6 \cdot 1 = -6 \][/tex]
Thus, the [tex]$y$[/tex]-intercept of [tex]\( f(x) \)[/tex] is [tex]\( -6 \)[/tex].
2. Determine the [tex]$y$[/tex]-intercept of [tex]\( g(x) \)[/tex]:
From the given table, the value of [tex]\( g(x) \)[/tex] when [tex]\( x = 0 \)[/tex] is [tex]\( -3 \)[/tex].
[tex]\[ g(0) = -3 \][/tex]
Thus, the [tex]$y$[/tex]-intercept of [tex]\( g(x) \)[/tex] is [tex]\( -3 \)[/tex].
3. Compare the [tex]$y$[/tex]-intercepts:
- [tex]\( y \)[/tex]-intercept of [tex]\( f(x) = -6 \)[/tex]
- [tex]\( y \)[/tex]-intercept of [tex]\( g(x) = -3 \)[/tex]
Now, we need to check the given comparisons:
- The [tex]$y$[/tex]-intercept of [tex]\( f(x) \)[/tex] is equal to the [tex]$y$[/tex]-intercept of [tex]\( g(x) \)[/tex].
[tex]\[ -6 = -3 \quad \text{(False)} \][/tex]
- The [tex]$y$[/tex]-intercept of [tex]\( f(x) \)[/tex] is equal to 2 times the [tex]$y$[/tex]-intercept of [tex]\( g(x) \)[/tex].
[tex]\[ -6 = 2 \cdot (-3) = -6 \quad \text{(True)} \][/tex]
- The [tex]$y$[/tex]-intercept of [tex]\( g(x) \)[/tex] is equal to 2 times the [tex]$y$[/tex]-intercept of [tex]\( f(x) \)[/tex].
[tex]\[ -3 = 2 \cdot (-6) = -12 \quad \text{(False)} \][/tex]
- The [tex]$y$[/tex]-intercept of [tex]\( g(x) \)[/tex] is equal to 2 plus the [tex]$y$[/tex]-intercept of [tex]\( f(x) \)[/tex].
[tex]\[ -3 = -6 + 2 = -4 \quad \text{(False)} \][/tex]
Therefore, the correct comparison is:
[tex]\[ \text{The $y$-intercept of \( f(x) \) is equal to 2 times the $y$-intercept of \( g(x) \)}. \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.